Sonographic Location of the Radial Nerve Confirmed by Nerve Stimulation During Axillary Brachial Plexus Blockade. Issue 5 (1st August 2009) - Wong, Daniel M.; Gledhill, Sam; Thomas, Rowan; Barrington, Michael J.
Abstract : Background and Objectives: Visualization of the radial nerve can be a challenge during ultrasound-guided axillary blockade. The objective of this study was to plot the location and examine the sonographic appearance of the radial nerve in the axilla using both ultrasound visualization and nerve stimulator verification in patients undergoing axillary blockade. Methods: Fifty-one patients requiring an axillary block for surgery were enrolled. Sonograms of the radial nerve at the point of best nerve stimulator response were recorded. The needle tip and center of the radial nerve were both plotted on a 2-dimensional scattergram using coordinates relative to the center of the axillary artery. A video tracing the path of the radial nerve was also recorded. Results: The radial nerve location was confirmed with both ultrasound imaging and nerve stimulation in 46 patients (90%). Five nerves (11%) were immediately deep to the axillary artery (ie, at a 6-o'clock position), 6 (13%) were cephalad, and the remaining 35 (76%) were caudad to the axillary artery. The 2-dimensional (2D) scattergrams reveal the variability in radial nerve location and clarity, of which 14 (30%) of the 46 visible nerves were difficult to trace precisely. A fascial plane between the medial and long heads of the triceps containing the radial nerve could be imaged clearly in 41 (91%) of the videos. Conclusions: The radial nerve uncommonly lies immediately deep to the axillary artery. It is frequently located on the caudad side of the artery.